The Integration of Psychology in Digital Da'wah Strategies as a Medium for Islamic Education - Muhammad Yudi Ali Akbar; Giri Cahyono; Dede Fahruroji; Mudrikatul Arafah (Jurnal Studi Pendidikan Agama Islam, 2026)
This study examines the integration of psychological principles into digital daʿwah strategies as an effective medium for Islamic education in the modern era. The rapid development of social media and digital technology has transformed the way religious messages are delivered and received, particularly among younger audiences. By incorporating psychological approaches such as understanding audience behavior, motivation, emotional engagement, and cognitive processes, digital daʿwah can become more persuasive, relevant, and impactful. This research employs a qualitative approach through systematic literature review and analysis of contemporary digital daʿwah practices. The findings suggest that the application of psychology in content design, communication style, and message framing enhances audience engagement and facilitates deeper understanding of Islamic teachings. Furthermore, digital platforms offer interactive and accessible spaces that support continuous learning and spiritual development. The integration of psychology into digital daʿwah strategies plays a crucial role in strengthening Islamic education by making it more adaptive, engaging, and responsive to the needs of the digital generation. This approach not only improves the effectiveness of daʿwah but also contributes to the formation of positive attitudes and behaviors aligned with Islamic values.